2015
DOI: 10.1371/journal.pone.0143693
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Posture and Vergence Eye Movements in Quiet Stance: Effects of Thin Plantar Inserts

Abstract: The purpose of this study was to assess properties of vergence and saccade eye movements as well as posture in quiet stance, and the effects of thin plantar inserts upon postural and oculomotor control. The performances of 36 young healthy subjects were recorded by a force platform and an eye tracker in three testing conditions: without plantar stimulation, with a 3 millimetre-thick plantar insert, either a Medial or a Lateral Arch Support (MAS / LAS). The results showed a decrease of the Surface and Variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
4
21
0
Order By: Relevance
“…Studies show that plant reliefs generate changes in body stabilization 14 , which legitimizes the decrease in oscillations and the speed of the pressure center seen in the analyses of this study. Similar to Mantovani et al 15 , in which the values of the mean anteroposterior oscillation before, during and after the use of insoles showed a reduction in the initial values, even without significant difference.…”
Section: Discussionsupporting
confidence: 64%
“…Studies show that plant reliefs generate changes in body stabilization 14 , which legitimizes the decrease in oscillations and the speed of the pressure center seen in the analyses of this study. Similar to Mantovani et al 15 , in which the values of the mean anteroposterior oscillation before, during and after the use of insoles showed a reduction in the initial values, even without significant difference.…”
Section: Discussionsupporting
confidence: 64%
“…In our initial experiment (Foisy et al, 2015 ), the postural and oculomotor performances of the subjects were recorded using a force platform and an eye-tracker. The following section summarizes the experimental paradigm of that first experiment, the details of which can be found in the original publication.…”
Section: Methodsmentioning
confidence: 99%
“…Erkelens et al ( 1989 ) also showed that vergence accuracy is best during body movements. This led us to investigate the effects of thin plantar inserts on both posture and eye movement control in an ecologic situation during which young and healthy subjects were performing saccade end vergence eye movements while being standing (Foisy et al, 2015 ). The results of this first experiment showed a decrease in the Surface area and Variance of Speed of the Center Of Pressure (CoP) displacements when the subjects were standing on a bilateral 3-mm-high Medial Arch Support (MAS) or Lateral Arch Support (LAS).…”
Section: Introductionmentioning
confidence: 99%
“…We put forward that somatosensory cues are normally used both for balance and vergence control, common zones of the CNS able to exchange information arising from feet and eye inputs (Foisy, Gaertner, Matheron, & Kapoula, ; Foisy & Kapoula, ). The existence of such common integration zones had already been suggested by other authors: Hollands, Marple‐Horvat, Henkes, and Rowan (), Hollands, Ziarva, and Bronstein () proposed the cerebellum or the superior colliculus; and more recently, several studies have shown that cross‐sensory interactions are common in primary cortical areas, most especially in early visual cortex (V1) for visual‐tactile interactions (Lunghi & Alais, ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the group comparisons’ results showed that, at 40 cm, the PEIS have a significantly lower RQ than the NPQS, except on Dépron ® , suggesting that the AB ® does not suppress the visual‐podal asynergy contrary to Dépron ® . It may be due to the fact that the plantar insert increases the feet tactile signal (Foisy et al., ), while foam lessens it (Yi & Park, ). In the situation of visual‐podal asynergy, additional information must be more difficult for the CNS to process than the attenuation of a peripheral noisy source of afferents.…”
Section: Discussionmentioning
confidence: 99%